On Botulinum Neurotoxin Variability - Cesare Montecucco (American Society for Microbiology, 2015)
ABSTRACT  The rapidly growing number of botulinum neurotoxin sequences poses the problem of the possible evolutionary significance of the variability of these superpotent neurotoxins for toxin-producing Clostridium species. To progress in the understanding of this remarkable phenomenon, we suggest that researchers should (i) abandon an anthropocentric view of these neurotoxins as human botulism-causing agents or as human therapeutics, (ii) begin to investigate in depth the role of botulinum neurotoxins in animal botulism in the wilderness, and (iii) devote large efforts to next-generation sequencing of soil samples to identify novel botulinum neurotoxins. In order to compare the fitness of the different toxins, we suggest that assays of all the steps from toxin production to animal death should be performed.